Should Social Value Obligations be Local or Global?. (February 2017) - Nayak, Rahul; Shah, Seema K.
Abstract: According to prominent bioethics scholars and international guidelines, researchers and sponsors have obligations to ensure that the products of their research are reasonably available to research participants and their communities. In other words, the claim is that research is unethical unless it has local social value. In this article, we argue that the existing conception of reasonable availability should be replaced with a social value obligation that extends to the global poor (and not just research participants and host communities). To the extent the social value requirement has been understood as geographically constrained to the communities that host research and the countries that can afford the products of research, it has neglected to include the global poor as members of the relevant society. We argue that a new conception of social value obligations is needed for two reasons. First, duties of global beneficence give reason for researchers, sponsors, and institutions to take steps to make their products more widely accessible. Second, public commitments made by many institutions acknowledge and engender responsibilities to make the products of research more accessible to the global poor. Future research is needed to help researchers and sponsors discharge these obligations in ways that unlock their full potential.